Effects on Structural Morphological and Optical Properties Pure and CuO/ZnO Nanocomposite - Sable, Pradip; Thabet, Nabeel; Yaseen, Jameel; Dharne, Gopichand (Trends in Sciences, 2022)
In the present work, synthesis of CuO, ZnO and CuO/ZnO Nonocomposites and their properties have been investigated. CuO, ZnO and CuO/ZnO NC were synthesized using the co-precipitation method. The nanocomposite materials were structural, morphological and optical properties characterized by X-ray diffraction (XRD), Field Emission Scanning Electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), UV-Vis Spectroscopy. The results of the XRD analysis exhibited that the pure CuO, ZnO and CuO/ZnO NC has a nanometer size with an average of 15.19 nm. The UV-vis analysis showed that the CuO, ZnO and CuO/ZnO NC has a band-gap of 3.31 and 2.35 eV. FTIR investigation revealed that the vibration of ZnO was observed at 561 cm-1 whereas CuO was at 602 cm-1 and composites 612 cm-1. The FESEM-EDX analysis revealed that the ZnO has a hexagonal structure whereas the CuO has a monoclinic structure. HIGHLIGHTS Present investigation deals with CuO, ZnO, and CuO/ZnO composites nanoparticles harvested as Co-Precipitation Method Various characterisation techniques were used to investigate the structural, optical, and morphological features of produced nanoparticles composites Investigation the effects of different properties of the CuO, ZnO and CuO/ZnO composites nanoparticles as well as Co-Precipitation method GRAPHICAL ABSTRACT